Improving Vocational Skills in Making Wall Decorations from Ice Cream Sticks Through Explicit Instruction Models for Children with Mild Mental Disabilities - Aryati, Devia (Inovan Publisher, 2024)
This research is based on the problems found in class VIII SLB WacanaAsih, in one practice room there are five students with mild mental retardation and there are two students who are not yet skilled in the skills of making wall decorations from ice sticks. Previously, children had learned skills from ice sticks such as making a pencil case for auspidol but were unsuccessful in the process, therefore this research was conducted using ice sticks through the explicit instruction model, in this study it will be carried out with two cycles, each cycle consists of: planning, implementation of actions, observation and reflection. The data collection techniques used are observation, documentation, and performance tests. Based on the results obtained by students using two cycles, namely the Ga value in cycle I action is 88.7%, and in cycle II obtained a value of 91.9%, while Ge students obtained a value in cycle I of 64.5%, and in cycle II obtained a value of 82.3%, Gi students in cycle I action are 88.7%, and in cycle II obtained a value of 91.9%, Fa students in cycle I action are 88.7%, and in cycle II obtained a value of 91.9%, and Pu students in cycle I action are 74.2%, and in cycle II obtained a value of 85.5%. Based on the data above, the conclusion of the skill of making wall decorations from ice sticks has increased significantly through the explicit instruction model.